Entre Pierre I-er et Etienne le Grand / Between Pierre Ist and Stephen the Great - Tereza Sinigalia (Anastasis: Research in Medieval Culture and Art)
Archaeological investigations and the restoration in progress of mural paintings confirm that the founder of the existing St. Nicolas Church in Rădăuți was Peter the Ist Mușat. It was the first prince of Moldavia here. His image could be seen in the Votive painting in the nave offering the model of the church to Christ, by intercession of St. Nicolas. He is followed by Bogdan, Stephen’s the Great last son, Stephen itself, his elder son Alexander and the princess Maria Voichita, Stephan’s third wife. Stephen the Great was the donor of the mural ensemble around 1490. The iconographic program has some important peculiarities: The Passion of Christ is missing and the Military Saints, too; a great number of medallions with Bishops is painted all around the first register of painting and a large suite pf Monks is to be found in the lower register. In the same register, on the eastern wall, an Imperial Deesis, with the Virgin carrying a royal crown, is completed by the figures of Saints Nicolas and John Chrysostomos. At the level of the vaults the most important compositions are the Glorifying of Christ and a Glorying of the Virgin and an unusual for this space, an Ecumenical Council.